Change in Objective Measure of Empathic Accuracy Following Social Cognitive Training - Haut, Kristen M.; Dodell-Feder, David; Guty, Erin; Nahum, Mor; Hooker, Christine I. (Frontiers in Psychiatry, 2019)
Background: The capacity for empathy plays an important role in interpersonal relationships and social functioning and impairments in empathy can have negative effects on social interactions and overall social adjustment. This suggests that empathy may be a critical target for intervention in individuals who struggle with social interactions, yet it is unclear if the skills required for empathy are malleable. This study investigates the efficacy of targeted social cognitive training for improving empathic skills. Methods: 45 individuals (mean age = 24) were included in this study. 24 individuals were allocated to the active social cognition training group and 21 individuals were allocated to a computer games control condition. Subjects completed approximately 10.5 hours of training over two weeks. Pre- and post- training, they completed measures of empathy and emotion recognition, including the Interpersonal Reactivity Inventory (IRI) and the Empathic Accuracy task. ANOVA and regression analyses testing changes in participants’ performance on the empathic accuracy task and scores on the IRI subscales were used to assess the effect of the social cognitive training. Results: Repeated measures ANOVA show that there is a significant group by timepoint interaction (F=4.254, p=.04) on the Empathic Accuracy task, with individuals who completed the social cognition training showing a significant improvement in performance following training. There were no significant changes for either group on any of the self-report IRI subscales. Individuals in the active training group showing significant improvement on negative valence videos and trend towards improvement on positive valence videos. In addition, individuals in the active training group who reported higher intrinsic motivation demonstrated greater improvement on the Empathic Accuracy task. Conclusions: Individuals who completed a computerized social cognition training program demonstrated improved performance on an objective task of empathic accuracy while individuals who completed a computer game control condition did not demonstrate any significant changes in their performance on the empathic accuracy task. These results suggest that targeted training in social cognition may increase empathic abilities, even in healthy individuals, and that this training may be beneficial to individuals with social cognitive deficits.